2015
DOI: 10.1038/srep13257
|View full text |Cite|
|
Sign up to set email alerts
|

Mice repeatedly exposed to Group-A β-Haemolytic Streptococcus show perseverative behaviors, impaired sensorimotor gating and immune activation in rostral diencephalon

Abstract: Repeated exposure to Group-A β-Haemolytic Streptococcus (GAS) may constitute a vulnerability factor in the onset and course of pediatric motor disturbances. GAS infections/colonization can stimulate the production of antibodies, which may cross the blood brain barrier, target selected brain areas (e.g. basal ganglia), and exacerbate motor alterations. Here, we exposed developing SJL male mice to four injections with a GAS homogenate and evaluated the following domains: motor coordination; general locomotion; r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
40
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(46 citation statements)
references
References 85 publications
6
40
0
Order By: Relevance
“…These observations are in line with pharmacological evidence indicating that several serotonergic agonists may constitute an effective treatment for the GABHS-dependent psychiatric symptoms (Swedo and Grant, 2005 ; Murphy et al, 2010 ). Additionally, these results parallel our study in which we showed that active streptococcal immunization throughout development may alter serotonergic transmission in the adult brain (Macrì et al, 2015 ). In the same study, Lotan et al ( 2014 ) addressed whether the antibodies produced in response to GABHS were sufficient to induce an abnormal phenotype.…”
Section: Preclinical Animal Models and Autoimmunitysupporting
confidence: 90%
See 3 more Smart Citations
“…These observations are in line with pharmacological evidence indicating that several serotonergic agonists may constitute an effective treatment for the GABHS-dependent psychiatric symptoms (Swedo and Grant, 2005 ; Murphy et al, 2010 ). Additionally, these results parallel our study in which we showed that active streptococcal immunization throughout development may alter serotonergic transmission in the adult brain (Macrì et al, 2015 ). In the same study, Lotan et al ( 2014 ) addressed whether the antibodies produced in response to GABHS were sufficient to induce an abnormal phenotype.…”
Section: Preclinical Animal Models and Autoimmunitysupporting
confidence: 90%
“…Other experimental studies, using a different approach based on active immunization, reported that streptococcal infections may trigger, in the presence of a vulnerable BBB, basal ganglia dysfunctions (Swerdlow and Sutherland, 2005 ). These studies show that streptococcus exposure may favor the onset of behavioral disturbances and neurochemical alterations, thereby providing additional information regarding PANDAS etiology (Hoffman et al, 2004 ; Yaddanapudi et al, 2010 ; Brimberg et al, 2012 ; Macrì et al, 2015 ). These results may support the hypothesis that antibodies produced in response to streptococcus infections may bind, in a context of BBB permeability, brain targets at the level of basal ganglia, causing the onset of behavioral and motor disturbances and neurochemical alterations (Martino et al, 2009 ).…”
Section: Preclinical Animal Models and Autoimmunitymentioning
confidence: 94%
See 2 more Smart Citations
“…Animal studies using mouse models have demonstrated that serum immunoglobulin G (IgG) is principally deposited inside the hippocampus, deep cerebellar nuclei, or rostral diencephalon, and that very low levels of IgG are present in the basal ganglia. [10][11][12] However, significant IgG deposition has been observed in the prefrontal cortex and basal ganglia in a rat model. 13,14 This bears a closer similarity to the human disease in which neuroimaging studies have shown powerful evidence of neuroinflammation in the basal ganglia and thalamus.…”
Section: Introductionmentioning
confidence: 99%